2018
DOI: 10.1037/xge0000365
|View full text |Cite
|
Sign up to set email alerts
|

The role of a “common is moral” heuristic in the stability and change of moral norms.

Abstract: Moral norms are fundamental for virtually all social interactions, including cooperation. Moral norms develop and change, but the mechanisms underlying when, and how, such changes occur are not well-described by theories of moral psychology. We tested, and confirmed, the hypothesis that the commonness of an observed behavior consistently influences its moral status, which we refer to as the common is moral (CIM) heuristic. In 9 experiments, we used an experimental model of dynamic social interaction that manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 81 publications
8
86
1
1
Order By: Relevance
“…Providing empirical information will often make people conclude that common, widespread behavior (good or bad) is acceptable, at a minimum, and often even approved of. Our result is in line with recent work showing that commonness of observed behavior influences its moral status (Lindström et al, 2018). For example, it has been shown that when tax evasion is perceived as more common, it will also be seen as more acceptable, which in turn influences its prevalence (Eriksson et al, 2015).…”
Section: ** ***supporting
confidence: 92%
See 1 more Smart Citation
“…Providing empirical information will often make people conclude that common, widespread behavior (good or bad) is acceptable, at a minimum, and often even approved of. Our result is in line with recent work showing that commonness of observed behavior influences its moral status (Lindström et al, 2018). For example, it has been shown that when tax evasion is perceived as more common, it will also be seen as more acceptable, which in turn influences its prevalence (Eriksson et al, 2015).…”
Section: ** ***supporting
confidence: 92%
“…Publicizing any behavior, whether good or bad, may lead the receiver to conclude that the behavior is also approved of. In this case empirical information leads to parallel normative conclusions (Eriksson et al, 2015;Lindström et al, 2018;Bicchieri et al, 2019b). Conversely, when getting normative information about common approval of good behavior, one may not infer that most people behave in the appropriate way.…”
Section: Introductionmentioning
confidence: 99%
“…, indicating that the more "on-target" the effect of an action in violating a given function, the more harshly that action was judged. Action likelihood was also negatively correlated with moral wrongness judgments (p < .001, 95% CI [-.21, -.18]), indicating that rarer actions were judged more harshly, consistent with past research (47). These results are robust when controlling for demographic factors.…”
Section: Cooperative Norms Predict Relationship-specific Moral Judgmesupporting
confidence: 84%
“…Nearly 300 years later, a rich body of empirical evidence substantiates Hume's observation. When told that a behavior is common, people infer that it is moral (Lindström, Jangard, Selbing, & Olsson, 2018), and when told that a behavior is moral, people infer that it is common (Eriksson, Strimling, & Coultas, 2015). Perceptions of commonality and morality are inextricably linked (Bear & Knobe, 2017).…”
Section: Moralitymentioning
confidence: 99%